Radiographic and histological study of perennial bone defect repair in rat calvaria after treatment with blocks of porous bovine organic graft material (Journal of Applied Oral Science, 2004)
Over the last few years, various bone graft materials of bovine origin to be used in oromaxillofacial surgeries have entered the market. In the present study, we determined the capacity of a block organic bone graft material (Gen-ox, Baumer SA, Brazil) prepared from bovine cancellous bone to promote the repair of critical size bone injuries in rat calvaria. A transosseous defect measuring approximately 8mm in diameter was performed with a surgical trephine in the parietal bone of 25 rats. In 15 animals, the defects were filled with a block of graft material measuring 8mm in diameter and soaked in the animal's own blood, and in the other 10 animals the defects were only filled with blood clots. The calvariae of rats receiving the material were collected 1, 3 and 6 months after surgery, and those of animals receiving the blood clots were collected immediately and 6 months after surgery. During surgery, the graft material was found to be of easy handling and to adapt perfectly to the receptor bed after soaking in blood. The results showed that, in most animals treated, the material was slowly resorbed and served as a space filling and maintenance material, favoring angiogenesis, cell migration and adhesion, and bone neoformation from the borders of the lesion. However, a foreign body-type granulomatous reaction, with the presence of numerous giant cells preventing local bone neoformation, was observed in two animals of the 1-month subgroup and in one animal of the 3-month subgroup. These cases were interpreted as resulting from the absence of demineralization and the lack of removal of potential antigen factors during production of the biomaterial. We conclude that, with improvement in the quality control of the material production, block organic bone matrix will become a good alternative for bone defect repair in the oromaxillofacial region due to its high osteoconductive capacity.